Cardiac magnetic resonance identifies raised left ventricular filling pressure: prognostic implications. (4th May 2022) - Garg, Pankaj; Gosling, Rebecca; Swoboda, Peter; Jones, Rachel; Rothman, Alexander; Wild, Jim M; Kiely, David G; Condliffe, Robin; Alabed, Samer; Swift, Andrew J
Abstract: Aims: Non-invasive imaging is routinely used to estimate left ventricular (LV) filling pressure (LVFP) in heart failure (HF). Cardiovascular magnetic resonance (CMR) is emerging as an important imaging tool for sub-phenotyping HF. However, currently, LVFP cannot be estimated from CMR. This study sought to investigate (i) if CMR can estimate LVFP in patients with suspected HF and (ii) if CMR-modelled LVFP has prognostic power. Methods and results: Suspected HF patients underwent right heart catheterization (RHC), CMR and transthoracic echocardiography (TTE) (validation cohort only) within 24 h of each other. Right heart catheterization measured pulmonary capillary wedge pressure (PCWP) was used as a reference for LVFP. At follow-up, death was considered as the primary endpoint. We enrolled 835 patients (mean age: 65 ± 13 years, 40% male). In the derivation cohort ( n = 708, 85%), two CMR metrics were associated with RHC PCWP:LV mass and left atrial volume. When applied to the validation cohort ( n = 127, 15%), the correlation coefficient between RHC PCWP and CMR-modelled PCWP was 0.55 (95% confidence interval: 0.41–0.66, P < 0.0001). Cardiovascular magnetic resonance-modelled PCWP was superior to TTE in classifying patients as normal or raised filling pressures (76 vs. 25%). Cardiovascular magnetic resonance-modelled PCWP was associated with an increased risk of death (hazard ratio: 1.77, P < 0.001 ). At Kaplan–Meier analysis, CMR-modelled PCWP was comparable to RHC PCWP (≥15 mmHg) to predict survival at 7-year follow-up (35 vs. 37%, χ 2 = 0.41, P = 0.52). Conclusion: A physiological CMR model can estimate LVFP in patients with suspected HF. In addition, CMR-modelled LVFP has a prognostic role. Structured Graphical Abstract: Structured Graphical Abstract Patients presenting with breathlessness underwent TTE, CMR, and RHC. Cardiovascular magnetic resonance-modelled PCWP and TTE-estimated PCWP were both compared with invasively measured PCWP. The diagnostic accuracy of our CMR model was 71% compared with 25% for TTE. In cases where TTE was non-diagnostic (indeterminate or incorrect diagnosis), CMR correctly reclassified the correct diagnosis in 71%. Furthermore, CMR-derived PCWP was an independent predictor of survival. CMR, cardiac magnetic resonance; HF, heart failure; PCWP, pulmonary capillary wedge pressure; SOB, shortness of breath; TTE, transthoracic echocardiography; RHC, right heart catheterization .